Risk factors for hospital-acquired pneumonia in hip fracture patients: a systematic review and meta-analysis - Wei Yao; Xiaojia Sun; Wanyun Tang; Wei Wang; Qiaomei Lv; Wenbo Ding (BMC Musculoskeletal Disorders, 2024)
Abstract Objective This study aimed to systematically assess the incidence and risk factors for hospital-acquired pneumonia (HAP) in hip fracture patients by meta-analysis. Methods Systematically searched four English databases (PubMed, EMBASE, The Cochrane Library, and Web Of Science) and four Chinese databases (CNKI, CQVIP, Sinomed, and WAN FANG) from inception until 20 November 2023. All studies involving risk factors of HAP in patients with hip fractures were considered. Newcastle-Ottawa Scale was used to evaluate the quality of the included studies. The results were presented with the pooled odds ratio (OR) and 95% confidence interval (95% CI). Results Of 35 articles (337,818 patients) included in this study, the incidence of HAP was 89 per 1000 cases. Twenty-three risk factors were eventually involved in the meta-analysis, and 21 risk factors were significant. Our study has identified four significant risk factors (advanced age, preoperative time, COPD, and hypoalbuminemia) associated with HAP, as follows: Advanced age as a continuous variable (OR 1.07, 95% CI 1.05–1.10), Advanced age > 70 years (OR 2.34, 95% CI 1.77–3.09), Advanced age > 80 years (OR 2.98, 95% CI 2.06–4.31), Chronic obstructive pulmonary disease (COPD) (OR 3.44, 95% CI 2.83–4.19), Time from injury to operation as a continuous variable (OR 1.09, 95% CI 1.07–1.12), Time from injury to operation ≥48 h (OR 3.59, 95% CI 2.88–4.48), Hypoalbuminemia < 3.0 g/dL (OR 3.03, 95% CI 1.93–4.73), and Hypoalbuminemia < 3.5 g/dL (OR 2.68, 95% CI 2.15–3.36). However, it is important to note that all the studies included in our research were retrospective in nature, which introduces certain limitations to the level of evidence and the ability to establish causal inferences. Discussion Patients who have suffered hip fractures are at an increased risk of developing postoperative hospital-acquired pneumonia, which can lead to prolonged hospital stays and adverse clinical outcomes. Consequently, the identification of these risk factors offers novel insights and methodologies for healthcare professionals in terms of both prevention and treatment. Trial registration Registration number: INPLASY2022100091.